2023
DOI: 10.1088/1361-6498/acdfd7
|View full text |Cite
|
Sign up to set email alerts
|

The scientific basis for the use of the linear no-threshold (LNT) model at low doses and dose rates in radiological protection

Abstract: The Linear No-Threshold (LNT) model was introduced into the radiological protection system about 60 years ago, but this model and its use in radiation protection are still debated today. This article presents an overview of results on effects of exposure to low linear-energy-transfer (LET) radiation in radiobiology and epidemiology accumulated over the last decade and discusses their impact on the use of the LNT model in the assessment of radiation-related cancer risks at low doses. The knowledge acquired over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…In the field of radiological protection, a linear no-threshold model (LNT) is currently used to estimate the risk of cancer (and other stochastic effects) after LD of IR (reviewed by UNSCEAR 2021; Laurier et al 2023). Accordingly, some recent epidemiological studies showed an increase in cancer mortality in nuclear industry workers (Richardson et al 2023) or an increase in hematological cancer after a CT-scan (Bosch de Basea Gomez et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of radiological protection, a linear no-threshold model (LNT) is currently used to estimate the risk of cancer (and other stochastic effects) after LD of IR (reviewed by UNSCEAR 2021; Laurier et al 2023). Accordingly, some recent epidemiological studies showed an increase in cancer mortality in nuclear industry workers (Richardson et al 2023) or an increase in hematological cancer after a CT-scan (Bosch de Basea Gomez et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some recent epidemiological studies showed an increase in cancer mortality in nuclear industry workers (Richardson et al 2023) or an increase in hematological cancer after a CT-scan (Bosch de Basea Gomez et al 2023). However, other studies suggest other options, such as that the LNT model overestimates the risk of cancer after LD of IR, that there are different slopes of dose-response for LD and high doses, or even that there is a threshold below which no deleterious effects would exist (reviewed by Laurier et al 2023). The present study shows that, after a CT-scan dose, there are genotoxic and molecular effects and that these effects are different depending on the radiosensitivity of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Even if it is accurate the effects indicated are too low to be shown even by large population epidemiological studies 5 . However, a recent detailed review supports the continued use of the hypothesis (Laurier et al 2023). This does pose a question; if the impact of a collective radiation dose will not show up, even with careful epidemiological studies, should we concern ourselves with it?…”
Section: Costs and Benefits Of Protective Actionsmentioning
confidence: 99%
“…One of the consequences of this approach is model selection uncertainty, where the researcher needs to decide which of these models to use to analyze a particular radiation effects dataset, or perhaps use a weighted ensemble of several models 9,10 . Therefore, model-specific differences in assumed dose response shapes and their implications foster controversy [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%